Optimization of Conditions for the Synthesis and Oxidation of 5,8-Dimethoxy-2-methyl-3,4-dihydroisoquinolin-1(2H)-one into Novel 2-Methylisoquinoline-1,5,8(2H)-trione - Ali, Basharat; Ahmed, Faiz; Shafiq, Nusrat; Nasrula, Muhammad (Orbital: The Electronic Journal of Chemistry, 2020)
Due to stability issue of isoquinolone’s their N-methylation is a challenging task, achieved the synthesis of N-methylated 2-methylisoquinoline-1,5,8(2H)-trione using readily available precursor 2-(2,5-dimethoxyphenyl)ethanamine via multistep strategy, finally oxidation of 5,8-dimethoxy-2-methyl-3,4-dihydroisoquinolin-1(2H)-one with ceric ammonium nitrate (CAN) lead to target isoquinolone in good yield, further oxidation conditions in final step were optimized using different catalyst ratio, reaction time and temperature conditions. DOI: http://dx.doi.org/10.17807/orbital.v12i1.143